A flux-intensifying permanent magnet synchronous motor and its magnetic equivalent circuit model. (November 2022) - Zhao, Xiaokun; Kou, Baoquan; Huang, Changchuang; Zhang, Lu
Abstract: In this paper, a flux-intensifying permanent magnet synchronous motor (FIPMSM) and its magnetic equivalent circuit (MEC) model are proposed. First, the structure of the FIPMSM is introduced. Second, the dynamic MEC model of the FIPMSM is established, and the mesh analysis formulation algorithm is used to solve the MEC model. For complex structures such as the petal-shaped rotor and non-uniform air gap, the equivalent reluctance calculation method is presented. Then, the MEC model is used to rapidly estimate the flux linkage, back-electromotive force (EMF) and electromagnetic torque. Finally, the finite element model of the FIPMSM is established. A prototype is manufactured and tested. The MEC results are verified by the finite element analysis (FEA) method and the prototype experiments.